A study on the effectiveness of using pictures in learning English / Rosiah Abd. Aziz - Abd. Aziz, Rosiah (2002)
This study was carried out to investigate the effectiveness of using pictures in learning English amongst students in Sekolah Kebangsaan Pusat Dungun. Questionnaires developed by the researcher were distributed to 32 students of Year 5 Melur and 4 English Year 5 teachers of Sekolah Kebangsaan Pusat Dungun.